Interventions in Early Childhood Care and Education for Children with Special Needs - Singh, Sushma; Tandon, Mala; Bajpai, Amita (Journal of Neonatal Surgery, 2025)
Objectives: This study aims to critically evaluate the efficacy of early childhood care and education (ECCE) interventions for children aged 0–6 with special needs, including intellectual disabilities, autism spectrum disorder (ASD), and sensory impairments. It seeks to identify strategies that enhance developmental outcomes, address implementation challenges, and improve quality of life, providing insights for educators, caregivers, and policymakers working with this population. Methods: A systematic review was conducted following PRISMA guidelines, analyzing peer-reviewed studies published between 2015 and 2024. Literature was sourced from PubMed, ERIC, and PsycINFO using keywords such as "early childhood," "special needs," "intervention," "education," and "care." Inclusion criteria focused on empirical studies evaluating ECCE interventions for children with developmental disabilities. Data extraction covered intervention type, sample size, duration, and outcomes (e.g., cognitive, social, adaptive skills), with effect sizes calculated where feasible. A narrative synthesis was employed due to methodological diversity. Results: Thirty-two studies (n=4,872) revealed that behavioral interventions like Applied Behavior Analysis (ABA) yielded large effect sizes (d=1.2) in communication and social skills, while inclusive preschool programs (d=0.5–0.7) and parent-mediated therapies (d=0.8) improved adaptive and cognitive domains. Access disparities and fidelity issues were notable barriers. Conclusions: Multi-disciplinary, early interventions significantly enhance developmental trajectories for children with special needs, though global inequities in access highlight the need for scalable, culturally responsive solutions.